Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s00542-005-0574-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of a disk-spindle supported by a plain journal bearing and pivot bearing

Abstract: A hydrodynamic bearing is widely used for hard disk drives, and it is better than a ball bearing in terms of vibration suppression, noise reduction and shock resistance. However, its cost to performance ratio should be further improved. In this study we analyzed the stability of a disk-spindle assembly supported by a hydrodynamic plain journal bearing and a pivot bearing at the bottom of the shaft. As a result, we found that a half-frequency whirl of a vertical spindle caused by the plain journal bearing becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…As for stability characteristics, whirl instability does not occur for the designed bearings over all eccentricity ratios. Ono et al [2] analyzed the stability of a disk-spindle supported by a plain journal bearing, and pivot bearing increases quadratically as rotational speed increases. Zhou et al [3] studied the oil-film dynamic coefficients of a journal bearing using an experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…As for stability characteristics, whirl instability does not occur for the designed bearings over all eccentricity ratios. Ono et al [2] analyzed the stability of a disk-spindle supported by a plain journal bearing, and pivot bearing increases quadratically as rotational speed increases. Zhou et al [3] studied the oil-film dynamic coefficients of a journal bearing using an experimental method.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon and Shen (2005) presented a numerical model predicting the shock response of rotating-shaft spindle motor with nonlinear FDBs. Ono et al (2005) have studied the stability of journal bearings only corresponding to translation motion. They analyzed the stability of a disk-spindle assembly supported by hydrodynamic plain journal bearings and a pivot bearing at the bottom of the flexible shaft.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has been restricted to the stability of journal bearings only for the translation motion. Ono et al (2005) analyzed the stability of a disk-spindle assembly supported by hydrodynamic plain journal bearings and a pivot bearing at the bottom of the shaft, and they showed that the gyro effect could stabilize the half-frequency whirl of the disk-spindle assembly. However, their study was restricted to the translation and tilting motion of the rotor with the journal bearings in four degrees of freedom, i.e., x, y, h x and h y .…”
Section: Introductionmentioning
confidence: 99%